The Use of Drilling Techniques Integrated with Technology to Improve Students’ Vocabulary Mastery at An Elementary school in South Bali - Pramesti, Ni Putu Adinda Putri; Dewi, Kadek Sintya; Mahendrayana, Gede (English Education Department STKIP Agama Hindu Singaraja, 2024)
The research was conducted to improve students' vocabulary mastery by applying drilling techniques combined with technology through vocabulary video media at An Elementary school in South Bali and to find out students' responses to the use of drilling techniques. Data collection was conducted through interviews, vocabulary tests, and observations using Classroom Action Research (CAR), which involved 35 grade 4 students. The results showed that drilling techniques combined with technology through vocabulary videos were very effective for students to understand vocabulary well, as seen from the pre-test with a score of 64.43 to 75 in cycle I and 87 in cycle II, which successfully exceeded KKTP. The student responses were very positive because they felt motivated, and the classroom atmosphere became fun because it was balanced with audio visuals. From the implementation of this study, it can be concluded that the use of drilling techniques integrated with technology can improve the vocabulary mastery of grade 4 students.